POTENSI FETAL BOVINE SERUM PADA MODIFIKASI MEDIUM KULTUR JONES DALAM DIAGNOSIS Blastocystis hominis: STUDI MENGENAI GAMBARAN MORFOLOGI DAN UJI PH - Kadek Intan Arta Sarita; Putu Sathiya Adi Janendra; Kadek Indira Maheswari; Kadek Edy Sukarma; Made Bayu Permasutha; Made Kurnia Widiastuti Giri (JST (Jurnal Sains dan Teknologi), 2024)
Diarrhea is the third leading cause of death among children under the age of five worldwide. Diarrhea can result from bacterial infections, viral infections, or parasitic infestations that disrupt the functioning of the digestive system. Therefore, research on the morphology of Blastocystis hominis is necessary to aid in the diagnosis of diarrhea. This study is an experimental investigation conducted on Jones culture medium that has been altered with fetal bovine serum. The study consists of five trial groups with different volume: P1 (0.1 mL), P2 (0.5 mL), P3 (1.0 mL), P4 (1.5 mL), and P5 (2.0 mL). The morphological findings of Blastocystis hominis in each trial group, with pH averages P1 (7.29), P2 (7.27), P3 (7.30), dan P4 (7.31), were examined microscopically. The results were found to be optimal, with a statistical value of P>0.05 in the independent t-test. The P5 test group (6.15) differed significantly from the gold standard at P<0.001. The fetal bovine serum can be utilized for clinical reasons at a volume of 0.1 mL and a pH of 7.29, as it is already capable of displaying morphological results.